2016
DOI: 10.1002/bdd.2014
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of a proton‐coupled organic cation antiporter in the blood–brain barrier transport of amantadine

Abstract: The blood-to-brain transport of amantadine, a weak N-methyl-d-aspartate (NMDA) antagonist, has been shown previously to participate in the cationic drug-sensitive transport system across the mouse blood-brain barrier (BBB). The purpose of the present study was to characterize the influx transport system by means of both an in situ mouse brain perfusion technique and in vitro studies using rat immortalized brain capillary endothelial cells (GPNT). The observed concentration-dependent initial uptake rate of [(3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In this context, we focused in this work on proton-coupled organic cation (H þ /OC) antiporter, because we have already shown that this transporter recognizes various CNS-active drugs, including histamine H1 receptor antagonists (e.g., pyrialamine 3 and diphenhydramine 3 ), opioids (e.g., oxycodone, 4 tramadol, 5 and apomorphine 6 ), dopamine D2 receptor agonists (e.g., pramipexol 7 ), N-methyl-D-aspartate receptor antagonists (e.g., memantine 8 ), and nicotinic acetylcholine receptor agonists (e.g., nicotine 9 and varenicline 10 ). Other researchers have also reported the BBB transport of other CNS-acting drugs, such as clonidine, 11 cocaine, 12 naloxone 13 and amantadine 14 via the H þ /OC antiporter. These findings indicate that the H þ /OC antiporter has a broad range of substrate specificity, although its molecular entity has not yet been identified.…”
Section: Introductionmentioning
confidence: 95%
“…In this context, we focused in this work on proton-coupled organic cation (H þ /OC) antiporter, because we have already shown that this transporter recognizes various CNS-active drugs, including histamine H1 receptor antagonists (e.g., pyrialamine 3 and diphenhydramine 3 ), opioids (e.g., oxycodone, 4 tramadol, 5 and apomorphine 6 ), dopamine D2 receptor agonists (e.g., pramipexol 7 ), N-methyl-D-aspartate receptor antagonists (e.g., memantine 8 ), and nicotinic acetylcholine receptor agonists (e.g., nicotine 9 and varenicline 10 ). Other researchers have also reported the BBB transport of other CNS-acting drugs, such as clonidine, 11 cocaine, 12 naloxone 13 and amantadine 14 via the H þ /OC antiporter. These findings indicate that the H þ /OC antiporter has a broad range of substrate specificity, although its molecular entity has not yet been identified.…”
Section: Introductionmentioning
confidence: 95%
“…This patient told the treating neurologist that while talking amantadine hydrochloride 100 mg tablets to prevent the flu, she experienced a remarkable remission in her symptoms of rigidity, tremor, and akinesia [ 172 ]. Although the compound is hydrophilic it easily penetrates the blood-brain barrier, due to active transport probably via a proton-coupled organic cation antiporter [ 224 ]. Interestingly, there have been facts emerging, amantadine has a great variety of action in other indications such as multiple sclerosis, traumatic brain injury, cancer pain.…”
Section: Drug Repositioningmentioning
confidence: 99%
“…However, few studies have investigated the effects of hepatic inflammation on the penetration of basic (cationic) drugs into the brain via uptake transporters. Transporters such as OCT1/SLC22A1, OCT2/SLC22A2, OCT3/SLC22A3, multidrug and toxin extrusion (MATE/SLC47A), and novel organic cation transporter (OCTN1/SLC22A4 and OCTN2/SLC22A5) are involved the penetration of basic drugs into the brain ( Kang et al., 2006 ; Kubo et al., 2013 ; Okura et al., 2007 ), and unidentified proton-coupled organic cation (H + /OC) antiporters might be involved in the penetration of organic cations into the brain ( Auvity et al., 2017 ; Chapy et al., 2015 ; Kitamura et al., 2014 ; Kurosawa et al., 2017 ; Suzuki et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%